Acquired lacrimal sac fistula mimicking basal cell carcinoma. (5th June 2013) - Litwin, A.S.; Timlin, H.; Sagili, S.; Wright, M.; Malhotra, R.
Summary: Background Lacrimal sac fistulae can arise after an episode of dacryocystitis, usually forming below the medial canthus. Preceding symptoms of a watery eye with mucous discharge and a history or signs of inflammation are typical. Objectives To highlight the features of lacrimal sac fistulae and encourage readers to consider this in the differential diagnosis of apparently ulcerative medial canthal skin lesions. Methods We describe three patients with inferior‐medial canthal ulcerative skin lesions, all referred to ophthalmic plastic surgeons either by dermatologists or plastic surgeons, presumed clinically to have basal cell carcinoma (BCC). Results All three were in fact due to acquired lacrimal sac fistulae, and syringing of the nasolacrimal system confirmed the presence of a fistula. Conclusions These cases illustrate the importance of questioning patients about their previous ocular symptoms when dealing with less familiar periocular lesions. Abstract : What's already known about this topic? Basal cell carcinoma (BCC) is the most common skin malignancy. Lacrimal sac fistulae can arise below the medial canthus after an episode of dacryocystitis. What does this study add? The crusting associated with a lacrimal sac fistula can be mistaken for a BCC. A history of dacryocystitis followed by a discharging lesion in this area should raise the suspicion of lacrimal sac disease. Syringing of saline through the lower lid punctum with resultant egress through the fistula would confirm the diagnosis.